If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6k-9-2k=46
We move all terms to the left:
6k-9-2k-(46)=0
We add all the numbers together, and all the variables
4k-55=0
We move all terms containing k to the left, all other terms to the right
4k=55
k=55/4
k=13+3/4
| 6x-5x=7x+x-15 | | x/3+2x=1/3 | | u÷5=4 | | 62+x=37=180 | | s+-29=46 | | y=1.6*2.5^13 | | 30=-5y+3(y+6) | | 15q-3(4q-6)=3q+q-9q | | -160=-8(8-3a) | | 9=w+(−8) | | 8(3m+45)=2m-4 | | 1/4+6/8=n | | Y-(-10)=x-2 | | 10u=9+9u | | 3/10=(−5/2)x | | -7.56=1.29m | | 3=n+14/9 | | 10v=-140 | | 8-(1)/(3x=16) | | -18+z=40 | | -26=3(u-8)-5u | | 92.8=-15+z | | 9b-6=8+7b | | 7(p+3)+9=5(p+2)-30 | | 24+(9-2x)²=(4x-1)*(5+x) | | 5x+7=-3+3x+16 | | (5x+6)=(8x-39) | | -7x+12+8=2+x+10 | | -2x-3x=-6x+4 | | –2p=6p−8p | | 13=1+3p | | 3x+14=13x |